Input files used for the tutorials of the calorine package - Lindgren, Eric; Erhart, Paul (Chalmers University of Technology, 2024)
This record contains input files that are used in the notebooks and examples included in the documentation of the calorine package.

These files have been compiled from several different sources as referenced in the tables below.

NEP models

File
Source

nep-PbTe.txt
https://zenodo.org/records/10108287

nep-CsPbI3-SCAN.txt
https://zenodo.org/records/8014365/files/nep-CsPbCl3-SCAN.txt

nep-graphite-CX.txt
https://zenodo.org/records/7811021/files/nep-C-CX.txt

nep-dipole-PTAF.txt
https://zenodo.org/records/10255268

Structures

File
Source

CsPbI3-cubic-Pm-3m.xyz
https://zenodo.org/records/8014365/files/CsPbBr3-SCAN-cubic-Pm-3m.xyz

CsPbI3-delta-Pnma.xyz
https://zenodo.org/records/8014365/files/CsPbCl3-SCAN-delta-Pnma.xyz

CsPbI3-orthorhombic-Pnma.xyz
https://zenodo.org/records/8014365/files/CsPbBr3-SCAN-orthorhombic-Pnma.xyz

CsPbI3-tetragonal-I4mcm.xyz
https://zenodo.org/records/8014365/files/CsPbCl3-SCAN-tetragonal-I4mcm.xyz

CsPbI3-tetragonal-P4mbm.xyz
https://zenodo.org/records/8014365/files/CsPbBr3-SCAN-tetragonal-P4mbm.xyz

graphite-prim.xyz
n/a

PTAF-monomer.xyz
n/a
Keywords: Physical Sciences; Fysik